1994
DOI: 10.1016/0014-5793(94)00725-x
|View full text |Cite
|
Sign up to set email alerts
|

The melanocortin (MC3) receptor from rat hypothalamus: Photoaffinity labelling and binding of alanine‐substituted α‐MSH analogues

Abstract: Membrane preparations of cells expressing the cloned rat hypothalamus melanocortin receptor, MC3, have been photoaffinity labelled using a radiolabelled photoreactive analogue of a-MSH, ['251-Tyr2,Nle4,0-Phe7,ATB-Lys"]a-MSH. SDS-PAGE followed by autoradiography showed a single band at 53-56 kDa for the native receptor or 35 kDa after deglycosylated with PNGase F, consistent with the predicted cDNA sequence. Receptor binding studies with a-MSH, y-MSH and [Nle4,0-Phe'Ja-MSH established that a-MSH and y-MSH had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 18 publications
9
22
0
Order By: Relevance
“…This is in agreement with the observation that substitution of Pro 12 for Ala in ␣-MSH did not affect binding to the MC3R (22). This implies that the residue at this position is not essential for receptor binding but may be important for MC4R activation only.…”
Section: And [D-tyr 4 ]Mt-ii On Mc4r Mc4(267-282 Mc3) Mc4(y268i)supporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the observation that substitution of Pro 12 for Ala in ␣-MSH did not affect binding to the MC3R (22). This implies that the residue at this position is not essential for receptor binding but may be important for MC4R activation only.…”
Section: And [D-tyr 4 ]Mt-ii On Mc4r Mc4(267-282 Mc3) Mc4(y268i)supporting
confidence: 91%
“…Nevertheless, it has been demonstrated that HFRW (MSH (6 -9)) forms the core sequence of melanocortins, which is necessary to bind to all MC receptors (21)(22)(23). Ligand selectivity may therefore be determined by residues outside the core region either through a selective interaction with different receptor subtypes, by altering folding of the core sequence, or by a combination of both.…”
mentioning
confidence: 99%
“…The full length peptide possesses nonselective sub-nanomolar to nanomolar potencies at the MC1R, MC3R, MC4R, and MC5R [46, 47]. Alanine scans of α-MSH have also indicated the importance of the Met 4 , Phe 7 , Arg 8 , and Trp 9 positions for binding and functional activity at the mouse MC1R and rat MC3R [48, 49]. A 2016 report examining the cloned mouse receptors indicated that in addition to positions Met 4 , Phe 7 , Arg 8 , and Trp 9 , the Glu 5 and His 6 positions also affect functional activity [47].…”
Section: Classic Peptide Melanocortin Ligandsmentioning
confidence: 99%
“…The ARC POMC and NPY neurons project to various parts of the brain, e.g., the PVN, LH and perifornical hypothalamic region, all of which contain substantial numbers of MC3 and 4 receptors [39,52]. The projection from the ARC to the PVN is important for the regulation of neurons that produce corticotropic and thyrotropin releasing hormones (CRH and TRH, respectively) and for the modulation of sympathetic activity, both of which are significant mechanisms in energy metabolism ( [53], Fig.…”
Section: The Importance Of the Melanocortin System In Energy Homeostasismentioning
confidence: 99%